Controlador Fuzzy em FPGA para aplicação em sistemas inteligentes de navegação - Anjos, Hugo Leonardo Minanti dos (2018)
This work proposes the development and implementation of an intelligent navigation system using fuzzy logic, developed in the hardware description language VHDL, and its implementation using the development software Quartus II, from the manufacturer ALTERA. The proposed navigation system aims the prototype walk without colliding in any obstacle using, for this, three distance sensors located at the front and sides of the prototype, and moved by two direct current motors. The results of this work, obtained through simulation and practical implementation, were compared to the results obtained with the simulations made in MATLAB software.